Beyond stimulus versus austerity: pluralist capacity building in macroeconomics - Irene van Staveren (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2017)
In this article a pluralist teaching method in macroeconomics is explained with examples. It demonstrates why pluralist macro teaching is important and that it is feasible even at the introductory level. It shows how it can be carried out using five key economic theories: social economics, institutional economics, feminist economics, post-Keynesian economics and neoclassical economics. It briefly summarizes how such pluralist teaching can be carried out on topics such as macroeconomic flow, economic growth, trade, poverty and well-being, and money.
Keywords: A22; B50; 330; pluralism; textbooks; teaching